Pemanfaataan Abu Vulkanik Sebagai Substitusi Sebagian Semen pada Beton Alir - Conrad Esguerra Jordy Beoang; Nurul Rochmah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of using volcanic ash as a partial replacement for cement on the slump value of self-compacting concrete. The main issue examined is the decrease in slump value as the percentage of volcanic ash increases, which affects the flowability and workability of the concrete. The substitution variations used are 0%, 5%, 10%, 20%, and 25%, with the addition of 1.5% superplasticizer Sika Viscocrete-3115N to improve workability. The research method involves preparing self-compacting concrete specimens for each variation and testing them using the slump flow method in accordance with ASTM C143 standards. Data analysis is carried out by comparing the average slump values of each mixture variation. The results show that increasing the percentage of volcanic ash leads to a decrease in slump value. The mixture without substitution produces the highest slump value, while the 25% substitution results in the lowest due to the higher absorption capacity of volcanic ash, which reduces the mixture’s workability. Overall, volcanic ash can still be used within certain limits.